Interracial Trust between Black Doctoral Student Protégés and White Mentors - Brown, Eric Montrece; Grothaus, Tim (International Journal of Multicultural Education, 2021)
Psychologists have found that many Black persons in the United States have significant levels of mistrust of White persons. This serves as a protective factor in response to pervasive structural and systemic racism. Yet interracial trusting relationships exist. In this phenomenological study, 10 Black counseling doctoral students described their interracial trust experiences with White faculty and/or clinical supervisor mentors. The authors constructed six themes from the data: setting less rigid boundaries, practicing transparency, taking the initiative, being congruent, honoring the proteges’ strengths and experiences, and advocating for equity. Implications and strategies for supervisors and educators are shared.